LINGUISTIC FEATURES OF THE SPEECH GENRE “GRATITUDE” (Scientific journal of the Fergana State University, 2024)
This article is about the expressions of satisfaction of the speaker in the semantic field of the speech genre of expressing gratitude in a personal and collective way, such as recognition of someone, praise, expression of gratitude, gratitude, recognition of oneself obliged to someone's help, blessing, welcoming mention, bow, material and immaterial support, that is, moral encouragement.